Development and Validation of the Future-Oriented Coping Scale in a Collectivist Cultural Context - Hafizhah Nasywa Zahira; Idwan, Hanifah Fadila; Ilhami, Muhammad Rizqi; Fajariah, Meutia Anilfa; Yusup, Rissa Khalida; Sari, Novita; Zamzami, Naera Zhafira Azkiati (Psikoislamedia: Jurnal Psikologi, 2026)
Coping assessments in Indonesia often focus on only one or two aspects, which limits their ability to describe coping strategies across time. Schwarzer expands this perspective through future-oriented coping, which views coping as a continuous process shaped by past experiences, present conditions, and expectations about the future. This study develops a coping instrument based on Schwarzer’s four dimensions: Reactive, Anticipatory, Preventive, and Proactive Coping. A total of 210 participants aged 17 to 30 were recruited using quota sampling. From an initial pool of 40 items, 17 items were retained after statistical screening. The analyses included content validity, item–rest correlations, reliability testing, and confirmatory factor analysis. Results indicate strong reliability with an alpha value of 0.832 and good model fit shown by CFI 0.972, TLI 0.955, RMSEA 0.039, and SRMR 0.081. These findings support the validity and reliability of the instrument and demonstrate its usefulness for assessing coping related to past, present, and anticipated stress.